The McKittrick–Wheelock syndrome: a rare cause of curable diabetes. (1st May 2016) - Challis, Benjamin G; Lim, Chung Thong; Cluroe, Alison; Cameron, Ewen; O'Rahilly, Stephen
Summary: McKittrick–Wheelock syndrome (MWS) is a rare consequence of severe dehydration and electrolyte depletion due to mucinous diarrhoea secondary to a rectosigmoid villous adenoma. Reported cases of MWS commonly describe hypersecretion of mucinous diarrhoea in association with dehydration, hypokalaemia, hyponatraemia, hypochloraemia and pre-renal azotemia. Hyperglycaemia and diabetes are rarely reported manifestations of MWS. Herein we describe the case of a 59-year-old woman who presented with new-onset diabetes and severe electrolyte derangement due to a giant rectal villous adenoma. Subsequent endoscopic resection of the tumour cured her diabetes and normalised electrolytes. This case describes a rare cause of 'curable diabetes' and indicates hyperaldosteronism and/or whole-body potassium stores as important regulators of insulin secretion and glucose homeostasis. Learning points: McKittrick–Wheelock syndrome (MWS) is typically characterised by the triad of pre-renal failure, electrolyte derangement and chronic diarrhoea resulting from a secretory colonic neoplasm. Hyperglycaemia and new-onset diabetes are rare clinical manifestations of MWS. Hyperaldosteronism and/or hypokalaemia may worsen glucose tolerance in MWS. Aggressive replacement of fluid and electrolytes is the mainstay of acute management, with definitive treatment and complete reversal of the metabolic abnormalities being achieved by endoscopic or surgical resection of the neoplasm.